2007
DOI: 10.1007/s10902-007-9078-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Peace in a Thatched Hut—that is Happiness’: Subjective Wellbeing Among Peasants in Rural China

Abstract: China, Personal wellbeing index, Subjective wellbeing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 30 publications
11
43
5
1
Order By: Relevance
“…This is similar to previous studies (Appleton and Song 2008;Davey et al 2007;Dolan and Metcalfe 2012;Graham et al 2011;Jiang et al 2012;Mukuria and Brazier 2013). Furthermore, in our study we also investigated the association between five different dimensions of health and SWB and found the strongest association for the anxiety/depression dimension.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is similar to previous studies (Appleton and Song 2008;Davey et al 2007;Dolan and Metcalfe 2012;Graham et al 2011;Jiang et al 2012;Mukuria and Brazier 2013). Furthermore, in our study we also investigated the association between five different dimensions of health and SWB and found the strongest association for the anxiety/depression dimension.…”
Section: Discussionsupporting
confidence: 91%
“…However, although there is a large income gap between urban and rural areas (Davey et al 2007;Knight et al 2009;Knight and Gunatilaka 2010a), we found that the SWB was not higher in the urban counties for the eastern and middle areas. For the eastern area SWB was even higher in the rural than in the urban county.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Contrary to the Camfield et al (2009) finding of higher happiness in urban areas, Davey et al (2009) found that participants from a remote farming village in China reported life satisfaction that was comparable to urban Chinese samples. Their entire village sample had a low socio-economic status.…”
Section: Intra-national Subjective Well-being Research In the Developcontrasting
confidence: 90%